Alternative Local Government Policies in Overcoming Unemployment Case Study in DKI Jakarta Province - Arifin, Zaenal (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2023)
In February 2021, the Open Unemployment Rate (TPT) in DKI Jakarta Province reached 8.51 percent, this exceeds the national unemployment rate of 6.26 percent. This phenomenon is of serious concern to the DKI Jakarta Provincial Government, where the high open unemployment rate can become a worrying issue because the open unemployment rate (TPT) in Jakarta has increased more significantly compared to the percentage of unemployment at the national level. The purpose of writing this research is to prepare an Alternative Policy in the form of a Regional Action Plan for DKI Jakarta Province to overcome the problem of unemployment. This study utilizes the SWOT Analysis and TOWS Analysis methods. The results obtained based on the analysis and discussion are that the DKI Jakarta Provincial government can carry out many program activities to overcome the problem of unemployment in the DKI Jakarta Province Region, including an increase in the competitive ability of workers. This can be seen in the preparation table of program targets and activities. The benefits of this research are expected to increase labour competitiveness, realize job opportunities and industrial relations that are conducive to developing businesses, and improve worker welfare to reduce unemployment.